Accelerated discovery of new catalysts for oxygen evolution reaction - Mahmoud G. Ahmed (Nanyang Technological University, 2023)
Electrochemical water splitting is a promising method to generate hydrogen gas (H2) as a green chemical fuel. However, the efficiency of overall process is limited by the sluggish kinetics of water oxidation reaction or oxygen evolution reaction (OER). As a result, large overpotential values are required to drive the reaction which in turn cause an inevitable rise in the energy consumption and lead to lower energy conversion efficiencies. Thus, exploring efficient OER catalysts is of great importance for energy conversion and storage systems. Synthesis of multi-metal spinel-based oxides is an effective strategy to increase the conductivity and tune the electronic structure and thus improve the OER catalytic performance. However, the rational design of an optimal multi-metal oxide is challenging. Although some studies have reported the synthesis of multi-metal oxides, the coverage of compositional diversity space is limited. The possible number of combinations upon mixing three elements far exceed the number heretofore reported or even that are synthesized and tested by conventional methods.